PENGARUH PEMBERIAN MAKANAN INDEKS GLIKEMIK RENDAH ATAU TINGGI TERHADAP KELELAHAN OTOT ATLET BADMINTON - , BREVI ISTU PAMBUDI, Dr. rer. nat. dr. BJ. Istiti Kandarina ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background : Many badminton athletes prone to muscle fatigue during games or at practice. At the moment that is anaerobic exercise, such as badminton, cause fatigue due to a buildup of lactic acid in the muscles and blood. One of the efforts made to overcome muscle fatigue is with the selection of the right meal. Objective: To determine whether there is the effect low or high of glycemic index meal (GI) to muscle fatigue badminton athletes. Methods: Experimental studies with repeated measures design. Subjects are 20 male badminton athletes aged 19-25 years who meet the inclusion and exclusion criteria have been determined. In a separate time (a week), subjects given high or low GI meal, after 30 minutes made anaerobic shuttle test to assess muscle fatigue. Results: There are significant differences in glucose levels at the time after being given a low or high GI foods (p = 0.021) and after anaerobic shuttle test (p = 0.000). Lactate levels there are significant differences before anaerobic shuttle test (p = 0.007) and after anaerobic shuttle test (p = 0,02). Ingesting or and high IG meal effect on muscle fatigue index (p= 0.009). Conclusion: low or high glycemic index meal affect to muscle fatigue for badminton athletes.Low GI meal can delay muscle fatigue in badminton athletes.